(untitled) (GEOmedia, 2019)
At the half of July 2017, a big wildfire destroys a large area of Vesuvio and Mount Somma in the Vesuvio National Park. In this work, we have used Landsat8 multispectral set of images to study the area before and after the fire. We have used tiles of 05-05-2017 and 24-07-2017. On the set of the images, we have applied the DOS for pass from TOA (Top Of the Atmosphere) to BOA (Bottom Of the Atmosphere). After this correction, we have applied the Pansharpening with the aim of improving images resolution from 30m/px to 15m/px. Therefore we have estimate NDVI (Normalized Difference Vegetation Index), NBR (Normalized Burn Ratio) and temperature of the ground before and after the fire.